Letter to the Editor Regarding Biomarkers in aneurysmal subarachnoid hemorrhage: A short review (2023)
The recent article authored by Batista et al provides a concise overview of the primary biomarkers that hold significance in subarachnoid hemorrhage. However, in order to further enhance the comprehensive understanding of this condition, it is imperative to include an overview of two noteworthy biomarkers associated with vasospasm, which may occur in specific cases of aneurysmal subarachnoid hemorrhage (aSAH). These biomarkers are the calcitonin gene-related peptide (CGRP) and neuropeptide Y (NPY).